Relating trophic structure to mercury distribution in a Gulf of St Lawrence food web: From zooplankton to colonial seabirds using stable nitrogen and carbon isotope analysis - Lavoie, Raphael A (University of Ottawa (Canada), 2009)
Even at very low concentrations in the environment, mercury (Hg) has the potential to biomagnify in food chains reaching levels of concern in apex predators such as fish-eating seabirds. The aim of this study was to determine the trophic structure and the transfer of total mercury (THg) and methylmercury (MeHg) in a Gulf of St. Lawrence food web using stable nitrogen (delta 15N) and carbon (delta13C) isotope analysis. Since food is the main exposure route to Hg in organisms, I wanted to characterize and compare the diet of top level predator seabirds using traditional and novel techniques. I found that body weight, trophic level and lipid content of organisms were the best predictors of THg and MeHg in this food web. Although the influence of habitat on the overall Hg distribution in the food web was low, I was able to demonstrate an effect within taxonomical groups which indicates that sediments are a source of THg and MeHg in this ecosystem. Several organisms at the base of the food chain were above the MeHg threshold level for the protection of wildlife suggesting a potential threat for upper trophic level predators. Diet composition of seabirds determined using traditional and novel techniques led to similar and complementary results illustrating that these methods can be combined for future studies to monitor prey availability and to predict the exposure of consumers to Hg.
Keywords: Health Sciences, Toxicology.